2015
DOI: 10.1158/1078-0432.ccr-15-0485
|View full text |Cite
|
Sign up to set email alerts
|

The MEK1/2 Inhibitor Pimasertib Enhances Gemcitabine Efficacy in Pancreatic Cancer Models by Altering Ribonucleotide Reductase Subunit-1 (RRM1)

Abstract: Purpose: Gemcitabine, a nucleoside analogue, is an important treatment for locally advanced and metastatic pancreatic ductal adenocarcinoma (PDAC) but provides only modest survival benefit. Targeting downstream effectors of the RAS/ERK signaling pathway by direct inhibition of MEK1/2 proteins is a promising therapeutic strategy, as aberrant activation of this pathway occurs frequently in PDAC. In this study, the ability of pimasertib, a selective allosteric MEK1/2 inhibitor, to enhance gemcitabine efficacy was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Nonetheless, GEM treatment reduced viable Suit-2 T27N tumor cells by 4-fold compared to PBS-treated Suit-2 T27N tumors, and a similar fold reduction was seen in Suit-2 tumors treated with AZD6244 + GEM (Figure 4B). A recent study published by Vena et al [31] also showed that the efficacy of GEM treatment was enhanced in pancreatic cancer models when administered in combination with a MEK1/2 inhibitor, Pimasertib. This study proposed a mechanism independent of MV-release for the increased efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, GEM treatment reduced viable Suit-2 T27N tumor cells by 4-fold compared to PBS-treated Suit-2 T27N tumors, and a similar fold reduction was seen in Suit-2 tumors treated with AZD6244 + GEM (Figure 4B). A recent study published by Vena et al [31] also showed that the efficacy of GEM treatment was enhanced in pancreatic cancer models when administered in combination with a MEK1/2 inhibitor, Pimasertib. This study proposed a mechanism independent of MV-release for the increased efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown potent activity in cell lines and xenografts with an activated MAPK pathway, robust antitumour activity in mouse models of myeloma and colorectal cancer, and to be able to circumvent resistance to BRAF inhibition in human melanoma cells . Notably, pimasertib has been shown to sensitise tumour cells to the effects of other anticancer agents and to work synergistically with gemcitabine to delay tumour growth in a pancreatic cancer mouse model …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] It has shown potent activity in cell lines and xenografts with an activated MAPK pathway, 17,19,20 robust antitumour activity in mouse models of myeloma 17 and colorectal cancer, 19 and to be able to circumvent resistance to BRAF inhibition in human melanoma cells. 20 Notably, pimasertib has been shown to sensitise tumour cells to the effects of other anticancer agents 17,21 and to work synergistically with gemcitabine to delay tumour growth in a pancreatic cancer mouse model. 20 Given this preclinical evidence, a two-part study was designed to investigate pimasertib in combination with the standard-of-care therapy, gemcitabine, compared to gemcitabine alone as first-line treatment in patients with mPaCa.…”
Section: Introductionmentioning
confidence: 99%
“…Although hENT1 and RRM1 have been found to be associated with gemcitabine-resistant pancreatic cancer, the molecular mechanism remains to be elucidated. Previous reports have stated that Notch is involved in mediating hENT1 and RRM1, with PPARα and PPARγ mediating hENT1, AKT, phosphoinositide 3-kinase, RAS/ERT and mitogen-activated protein kinase kinase 1/2 mediating RRM1 (2529). The present study investigated whether the EMT transcriptional factors, TWIST1 and Slug, can suppress the expression of hENT1 and enhance the expression of RRM1 in GR-HPCCs.…”
Section: Discussionmentioning
confidence: 99%